In their words: listening to teachers' perceptions about stress in the workplace and how to address it. Issue 4 (8th August 2021) - Carroll, Annemaree; Flynn, Libby; O'Connor, Emma Sanders; Forrest, Kylee; Bower, Julie; Fynes-Clinton, Samuel; York, Ashley; Ziaei, Maryam
ABSTRACT: Teacher stress remains a consistently reported issue nationally and internationally in both the mainstream media and academic fora. Understanding the source/s of stress, however, remains complex given the interplay of external and internal factors that have the potential to shape teachers' stress and resilience responses. This exploratory qualitative study sought to understand 74 teachers' perceptions of the main contributors to stress in the workplace, and to investigate their beliefs about strategies to help ameliorate these stressors. Applied Thematic Analysis revealed a range of systemic, organisational, relational, and intrapersonal stressors as the driving forces behind the experiences of teacher stress in the workplace. In light of these findings, teacher's beliefs around how to best alleviate these stressors are discussed. Conclusions highlight the need for better systems and support in building and sustaining teacher resilience to help protect against teacher burnout.